International organizations : the politics and processes of global governance - Karns, Margaret P.; Mingst, Karen A., 1947-; Stiles, Kendall W. (Boulder, Colorado : Lynne Rienner Publishers, Inc., 2015)
The third edition of the award-winning International Organizations has been thoroughly revised and updated to take into account new developments and shifting power relations since 2009, as well as the most current scholarship. As before, the authors provide a comprehensive, in-depth examination of the full range of international organizations. New features of the book include attention to a broader range of theoretical approaches, to the increasing importance of regional organizations, and to emerging forms of governance. And new case studies highlight the governance dilemmas posed by the Libyan and Syrian civil wars, human trafficking, LGBT rights, climate change, and more.--
1. The challenges of global governance -- 2. Theoretical foundations of global governance -- 3. IGOS and the foundations of global governance -- 4. The United Nations: centerpiece of global governance -- 5. Regional organizations -- 6. Nonstate actors: NGOs, networks, and social movements -- 7. The search for peace and security -- 8. Global economic governance -- 9. Promoting economic well-being and human development -- 10. Protective human rights -- 11. Protecting the environment -- 12. Dilemmas in global governance.
Includes bibliographical references and index.
Keywords: International agencies; International organization